Efficacy and safety of acupuncture monotherapy or combined with pelvic floor muscle training for female stress urinary incontinence: a systematic review and meta-analysis - Jiang, Tong; Dong, Zhi-Yu; Shi, Ying; Zhou, Yang-Qing; Zhang, Hong-Bin; Gong, Yi (Frontiers in Medicine, 2025)
BackgroundStress urinary incontinence (SUI) is involuntary urine leakage during effort. Pelvic floor muscle training (PFMT) is a common physical therapy for SUI, but has low adherence and its long—term effectiveness is uncertain. Drug therapy has side-effect problems and surgery has risks. Acupuncture’s role in improving SUI is also unclear based on previous studies.ObjectivesThis systematic review and meta-analysis evaluated the efficacy and safety of acupuncture individually or combined with PFMT in improving symptoms and women’s health-related quality of life of SUI.DesignA systematic review and meta-analysis were conducted.PatientsWomen with stress urinary incontinence were treated with electroacupuncture (EA) individually or acupuncture combined with PFMT.ResultsIn the analysis comparing urinary leakage 1 h and the ICIQ-SF score, electroacupuncture (EA) intervention was significantly associated with improvements in both urine leakage (MD = 4.69, 95% CI 2.83 to 6.55, I2 = 62%) and ICIQ-SF (MD = 2.61, 95% CI 1.64 to 3.58, I2 = 65%). The results were robust for the sensitivity analyses. EA was not associated with an increased incidence of adverse events compared to placebo EA (RR = 1.08, 95% CI 0.50 to 2.35, I2 = 0%). When comparing the group receiving pelvic floor muscle training (PFMT) combined with acupuncture to the PFMT only group, the combination therapy was found to improve urine leakage 1 h (MD = 1.91, 95% CI 0.96 to 2.86, I2 = 80%) and improve ICIQ-SF (MD = 2.63, 95% CI 1.60 to 3.65, I2 = 75%) in patients with SUI, despite significant heterogeneity observed. Subgroup analyses based on urine leakage 1 h revealed that subjects with mild stress urinary incontinence showed improvements (MD = 1.46, 95% CI 0.82 to 2.10, I2 = 58%), as did those with moderate stress urinary incontinence (MD = 4.9, 95% CI 1.72 to 8.08, I2 = 77%). There were significant differences between these subgroups (I2 = 77%, p = 0.04). In the subgroup analysis of intervention types, manual acupuncture showed no significant effect when combined (MD = 1.11, 95% CI -0.61 to 2.83, I2 = 86%).ConclusionThe findings from this meta-analysis indicate that EA is more effective at improving the clinical symptoms and quality of life in patients with SUI compared to placebo EA, and it does not increase the risk of adverse events. Moreover, the therapeutic effect of SUI treatment with EA combined with pelvic floor muscle training (PFMT) elicits a more positive response than PFMT alone. This suggests that EA, either as a standalone therapy or as an adjunct to PFMT, can offer beneficial outcomes for individuals with stress urinary incontinence, expanding the range of clinical treatment options available.Systematic Review RegistrationThe meta-analysis was registered in PROSPERO (CRD42022381409).